Analysis of constant-current electro-osmotic dewatering of various solid–liquid systems by considering the creep deformation - Iwata, Masashi; Jami, Mohammed Saedi (Elsevier Inc., 2007)
A constant-current electro-osmotic dewatering (EOD) of various solid–liquid systems is analyzed using the Terzaghi–Voigt combined model by considering the creep deformation of the material. Electro-osmotic dewatering experiments under constant electric current density of bentonite clay, KC-flock, zinc oxide and some of their mixtures are carried out. The basic differential equation based on the model is solved analytically by assuming that both electro-osmotic pressure gradient Epg and modified consolidation coefficient Ce of the material are constant. The solution can explain the time course of changes in solid compressive pressure distribution. The theory can also explain the final moisture distribution of the material. The progress of electro-osmotic dewatering can be represented by an average consolidation ratio Uc as in mechanical expression. Both Ce and Epg increase with an electric current density i. A larger Ce leads to a higher dewatering rate; a larger Epg results in a higher solid compressive pressure distribution in the material. It is found that the amount of creep deformation depends upon the dewatering rate; the faster the dewatering rate, the larger the creep deformation, i.e., the creep deformation is more remarkable when a higher current density is applied to the material. The effectiveness of EOD can be represented by the relative difference of the initial and final void ratios. Variations of the effectiveness of dewatering with the material composition, electric current density i, preconsolidation pressure ps1 and total solid volume per unit cross-sectional area ω0 are investigated. It is found that higher composition of charged material and higher current density show improved dewatering. For higher ω0, slight increase in effectiveness of dewatering is observed. For significant decrease of preconsolidation pressure, a relatively small increase in the effectiveness is observed. Therefore, among these, the material composition and current density are the main EOD parameters that can be used to determine the feasibility of EOD as efficient solid–liquid separation process.